2003
DOI: 10.1111/j.1471-0528.2003.02098.x
|View full text |Cite
|
Sign up to set email alerts
|

The differential expression of oestrogen receptors, progesterone receptors, Bcl‐2 and Ki67 in endometrial polyps

Abstract: Objective To obtain a greater understanding of the pathogenesis of endometrial polyps and to gain insight into which factors play a pivotal role in their growth. Design Retrospective analysis of archived paraffin-embedded specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
3
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 16 publications
1
46
3
4
Order By: Relevance
“…This suggests that expression of Ki-67 was more sensitive in reflecting the rate of cell proliferation in PCa tissues, which is similar to previous reports. 14,15 The Ki-67 antigen is useful for identifying proliferative cells. Although flow cytometry methods showed that Ki-67 is expressed in all cell cycle phases except G0 phase, its detection by immunohistochemical methods is limited to its appearance in the late G1 phase with maximum expression in prophasis and metaphases.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that expression of Ki-67 was more sensitive in reflecting the rate of cell proliferation in PCa tissues, which is similar to previous reports. 14,15 The Ki-67 antigen is useful for identifying proliferative cells. Although flow cytometry methods showed that Ki-67 is expressed in all cell cycle phases except G0 phase, its detection by immunohistochemical methods is limited to its appearance in the late G1 phase with maximum expression in prophasis and metaphases.…”
Section: Discussionmentioning
confidence: 99%
“…Los pólipos endometriales se originarían en la capa basal del endometrio y sus receptores serían similares a los de esta capa y sensibles por lo tanto, a la acción de los estrógenos y de la progesterona (Kurman et al). Se ha postulado que los pólipos podrían ser el resultado de una alteración cuantitativa a nivel de los receptores de estrógeno (RE) y de progesterona (RP) (Maia et al,1998;Mittal et al,1996;Taylor et al, 2003).…”
Section: Introductionunclassified
“…Se observó la presencia en el útero de receptores de estrógenos en sus dos isoformas alfa y beta (Artega et al,1998;Taylor et al;Critchley et al, 2001), llegándose a la conclusión que el principal receptor es el isoforma alfa. …”
Section: Introductionunclassified
“…Os pólipos endometriais são, portanto, caracterizados por aberrações de regiões especificas do cromossomo, as quais provavelmente envolvem genes relacionados ao processo proliferativo (Speleman F et al, 1991;Dal Cin P et al, 1992;Vanni R et al, 1995;Taylor LJ et al, 2003). A progressão de hiperplasia simples para complexa e, depois, para atípica, demora muitos anos e, possivelmente, depende de acúmulo de aberrações genéticas específicas.…”
Section: Valor Preditivo Positivounclassified
“…Essas alterações genéticas favorecem o crescimento do câncer por impedirem apoptose e, subsequentemente, por afetarem a regulação do "turnover" celular. A hipertensão também é um fator de risco estabelecido para pólipo endometrial com aspecto histológico pré-maligno e maligno (Vanni R et al,1995;Mertens et al, 2002;Taylor LJ et al, 2003).…”
Section: Valor Preditivo Positivounclassified